Design, operation, and performance evaluation of a cable‐drawn dual‐axis solar tracker compared to a fixed‐tilted system. Issue 6 (14th September 2015) - Lo, Summer; Cheng, Fritz; Chang, Vincent; Liu, William Der‐Jenq; Chang, Leo; Adurodija, Ojo F.; Chou, ErhNan; Lung, Curtis; Liu, Jeff; Lu, Tim; Su, Jeffery; Cheng, Eve
Abstract: This article discusses the design, operation, and performance evaluation of a unique cable‐operated 6.24 kWp commercial‐size solar tracking system called iPV dual‐axis tracker or iPV DAT with a position detector to gain the maximum power from the sunlight. Compared with other solar tracking systems, low cost, simplified hardware structure, and controlling algorithm are the advantages of this system. The operating method of the 6.24 kWp iPV DAT follow a simple pull and release of the steel cables connecting the corners of the PV module frame to the electric motors and directed by an electronic control system. The steel cables attached to the corners of the module frame also provide an extra stability in the event of high wind of up to 220 km/h. The accuracy of the tracking effect is managed by an astronomical algorithm that enables a full 360° azimuth rotation and altitude tilt of −40° to 40° (0 = horizontal). The controller algorithm also includes backtracking capability that allows optimization of ground cover ratio. Performance evaluation of the iPV DAT installed and operated in Taiwan for 12 months is compared with a fixed‐tilt PV system. An average electricity gain of 30.1% and performance ratio of 93% are realized using iPV DAT. Abstract : The design, operation, and performance evaluation of a cable‐drawn dual‐axis solar tracker compared to a fixed‐tilted system. Work is based on the development and application of an innovative 6.24 kWp commercial solar tracker (iPV) that uses drawn cables to drive position the PV array in the direction of the sun throughout the day. The iPV tracker is attempted to simplify and increasing the reliability of the solar tracking systems, thus lowering the operation and maintenance costs.